On the rhetoric of handmaidenhood: The translator’s construction of (im)modesty - Kelly Washbourne (MediAzioni)
The translator's positionality is not merely imposed by the public or literary stakeholders, but he or she has often been an active co-constructor of it. My claim goes beyond repeating the norm of self-effacement: translators to this day have staked the humble position in ways strikingly like those used by authors, making the humility topos, I argue, a writerly gesture. This work surveys the rhetoric of humility, its nuances and justifications, and diverse publics for whom these strategies are performed: authors, patrons, or readers. Ethos, persona, and hexis form part of the self-fashioning strategies that are also trust-building, and which often reveal slippages into self-assertions and even preemptive challenges. The practice extends well beyond early modern literature to the modern era, as I illustrate. I entertain whether humility is in fact the translator 'under erasure', not invisible but visible-in-invisibility. As modesty topoi are also shown to often be mere translation norms, “devotional formula”, or even immodesty in disguise, this work considers many of its ‘rhetorical moves’, complicating assumptions of the meek translator. Finally, I briefly delineate an ‘immodesty turn’ with perhaps ancient origins but found full-voiced in certain feminist translators. Forms of immodesty overtly assert authorhood and explicitly 'write back' against the rhetoric of the past.